Susceptibilidad del olmo (Ulmus pumila L.) y de cinco especies arbóreas nativas del centro-sur de la provincia de Córdoba (Argentina) a la infección por Pleurotus Ostreatus (Agaricales: Pleurotaceae) - Oggero, Antonia Josefina (2018)
Biological invasions advance on ecosystems causing major changes in their structure and ecological processes. Ulmus pumila L., is an exotic species that develops processes of invasion in Argentina and mechanical and chemical techniques have been used for its control in the affected sites. Biological control is now considerated as a new alternative. In the present work, the infection capacity of Pleurotus ostreatus on U. pumila plants was evaluated in order to collect and provide basic information to generate new options for biological control of U. pumila. Laboratory tests were carried out to determine the success of establishment of Pleurotus on cuttings of native tree species from the biogeographic district of Espinal and U. pumila. It was found that P. ostreatus had the ability to externally colonize all evaluated species although only in stakes of U. pumila could complete the life cycle. Finally, the anatomical study of the wood indicated that U. pumila is the species, among the studied ones, with greater proliferation of mycelium and even with formation of chlamydospores. In this way, it can be said that this exotic species is more susceptible to fungal infection than the native species studied.